Task-Correlated Cortical Asymmetry and Intra- and Inter-Hemispheric Separation. Issue 1 (December 2017) - Cohen, Yaniv; Wilson, Donald
Abstract Cerebral lateralization is expressed at both the structural and functional levels, and can exist as either a stable characteristic or as a dynamic feature during behavior and development. The anatomically relatively simple olfactory system demonstrates lateralization in both human and non-human animals. Here, we explored functional lateralization in both primary olfactory cortex – a region critical for odor memory and perception- and orbitofrontal cortex (OFC) – a region involved in reversal learning- in rats performing an odor learning and reversal task. We find significant asymmetry in both olfactory and orbitofrontal cortical odor-evoked activity, which is expressed in a performance- and task-dependent manner. The emergence of learning-dependent asymmetry during reversal learning was associated with decreased functional connectivity both between the bilateral OFC and between the OFC-olfactory cortex. The results suggest an inter-hemispheric asymmetry and olfactory cortical functional separation that may allow multiple, specialized processing circuits to emerge during a reversal task requiring behavioral flexibility.